Peroperative diagnosis of rhabdomyolysis - (:unkn) unknown (My University, 2005)
Crash syndrome or traumatic rhabdomyolysis constitutes the systemic changes seen after crash injury. The pressure causes necrosis of muscle, and during revascularisation diffusion of calcium, sodium and water into the muscle cells is seen, together with loss of potassium, phosphate, lactic acid, myoglobin and creatinine kinase. Untreated these changes can lead to: hyperkalemia, acidosis, acute renal failure and hypovolemic shock. This case report describes a patient developing rhabdomyolysis following fracture of femur. It was diagnosed and treated early during the course of anesthesia.
Keywords: Crush injury; Rhabdomyolysis